Religiusitas dan konsep diri akademik dengan stres akademik mahasiswa santri - Radisti, Mediska; Suyanti, Suyanti; Albadri, Albadri (PSYCOMEDIA : Jurnal Psikologi, 2023)
Academic stress is the type of stress most often experienced by students, especially those studying at Islamic boarding schools, because they have academic demands as students and santri. This study aims to determine the relationship between religiosity and academic self-concept and academic stress in students studying at Islamic boarding schools. This study uses a correlational quantitative approach. There were 114 students who participated in this study and were selected based on a simple random sampling technique. Data analysis used Sperman's Rho correlation technique because the normality assumption test results were not fulfilled. The results of the correlation test showed that there was a negative and significant relationship between religiosity and academic stress, and there was a negative but not significant relationship between academic self-concept and academic stress. This shows that there is a level of individual religiosity that plays a more significant role in academic stress than individual self-concept.